Pseudo-topotactic growth of diamond nanofibers. (1st October 2019) - Narayan, J.; Bhaumik, A.; Haque, A.
Abstract: We report pseudo-topotactic growth of single-crystal diamond fibers by nanosecond laser melting of amorphous carbon nanofibers (CNFs) and crystalline multi-wall carbon nanotubes (MWCNTs). A rapid laser melting in a super undercooled state and subsequent quenching convert the tips of CNFs and MWCNTs into phase-pure <110> nanodiamonds along the growth directions. Subsequent laser pluses melt regions below <110> nanodiamonds that provide seeds for epitaxial growth. By repeating this process, the length of <110> nanodiamond fibers can be increased, as each pulse results in ∼50 nm nanodiamond region, depending upon the initial size of CNFs and MWCTs. This conversion process can be carried at ambient temperature and pressure in air. The epitaxial nature of <110> nanodiamond fibers has been confirmed by systematic electron-back-scatter-diffraction studies along the fiber in high-resolution scanning electron microscopy, and high-resolution TEM imaging and diffraction. The nature of C–C bonding characteristics was studied by high-resolution electron-energy-loss spectroscopy to establish the formation of diamond phase by the characteristic peak at 292 eV for sp 3 bonding (σ ∗ ), and absence of 284 eV peak for sp 2 (π ∗ ) graphitic bonding. The characteristic diamond Raman peak at 1332 cm −1 is found to downshift to 1321 cm −1 because of phonon confinement in nanodiamonds associated with nanofibers. These nanodiamond structures can be doped with both n- and p-type dopants with concentrations far higher than thermodynamic solubility limit due to solute trapping during quenching from the liquid phase. Thus, these nanodiamond structures provide ideal platform for nanosensing, computing and communication, including efficient field emitting devices. Graphical abstract: Image 1